Pengaruh EPS, ROI Dan EVA Terhadap Return Saham Perusahaan Otomotif Di Bursa Efek Indonesia (BEI) - Ridwan Jazai; Edi Subiyantoro; Harmono Harmono (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
This research aims to know the influence of EPS, ROI and EVA against the stock return company automotive in indonesia stock exchange (idx) period of 2014 – 2017. This type of research using quantitative (Eksplanatory Research). The population of the research was a manufacturing company in particular the automotive industry by using purposive sampling methods, where there are sample amounted to 12 companies. Research data is secondary data obtained from annual report of manufacturing companies in particular the automotive industry from the year 2014-2017. Data analysis techniques using multiple linear regression. The results of this study indicate that the variable EPS, ROI and EVA simultaneously has effect significantly to stock return. While partially EPS positive effect significantly to stock return, ROI positive effect significantly to stock return but EVA has not positive effect significant against stock return.